Schedule of Mafic to Hybrid Magma Injections Into Crystallizing Felsic Magma Chambers and Resultant Geometry of Enclaves in Granites: New Field and Petrographic Observations From Ladakh Batholith, Trans-Himalaya, India - Kumar, Santosh (Frontiers in Earth Science, 2020)
Diorites, granites, and associated magmatic enclaves and dykes constitute the bulk of the Ladakh Batholith, which is an integral part of the Trans-Himalayan magmatic arc system. In this paper, geometry of microgranular enclaves hosted in the granites has been examined from the Leh-Sabu-Chang La and surrounding regions of the eastern Ladakh Batholith to infer the mechanism and schedule of mafic to hybrid magma injections into evolving felsic magma chambers and the resultant enclave geometry. Mafic and/or hybrid magmas injected into felsic magma at low volume fraction (<0.35) of crystals and form the rounded to elongated microgranular enclaves in the Ladakh Batholith. Angular to subangular (brecciated) rounded to elongated pillow-like microgranular enclave swarms can also be documented as disrupted synplutonic mafic to hybrid dykes and sheets, when intruding the felsic magma with high volume fraction (>0.65) of crystals. A large rheological difference between coeval felsic and mafic magmas inhibits much interaction. Mafic magma progressively crystallizes and evolves while minimizing thermal and rheological differences. Consequently, the felsic-mafic magma interaction process gradually becomes more efficient causing dispersion of enclave magma globules and undercooling into the partly crystalline felsic host magma. Thus, the evolution of the Ladakh Batholith should be viewed as multistage interactions of mafic to hybrid magmas coeval with felsic magma pulses in plutonic conditions from its initial to waning stages of evolution.